Electrodynamics of the Dielectrics (Global Journal of Science Frontier Research, 2018)
In the scientific literature is in sufficient detail opened the role of the kinetic inductance of charges in the conductors and the plasmo-like media, but it is not opened the role of this parameter in the electrodynamics of dielectrics. This parameter in the electrodynamics of dielectrics plays not less important role, than in the electrodynamics of conductors. In the article the electrodynamics of dielectrics taking into account the kinetic inductance of the charges, which form part of their atoms or molecules is examined. This most important question fell out from the field of the sight of scientists, and this article completes this deficiency.
Keywords: dielectric; conductor; kinetic inductance of charges; dispersion of dielectric constant; plasmo-like medium